Reduced B0/B1+ sensitivity in velocity‐selective inversion arterial spin labeling using adiabatic refocusing pulses - Bolar, Divya S.; Barnes, Ryan A.; Chen, Conan; Han, Fei; Pfeuffer, Josef; Liu, Thomas T.; Wong, Eric C. (Magnetic resonance in medicine, 2024)
Purpose To mitigate the B0/B1+ sensitivity of velocity‐selective inversion (VSI) pulse trains for velocity‐selective arterial spin labeling (VSASL) by implementing adiabatic refocusing. This approach aims to achieve artifact‐free VSI‐based perfusion imaging through single‐pair label‐control subtractions, reducing the need for the currently required four‐pair dynamic phase‐cycling (DPC) technique when using a velocity‐insensitive control. Methods We introduce a Fourier‐transform VSI (FT‐VSI) train that incorporates sinc‐modulated hard excitation pulses with MLEV‐8‐modulated adiabatic hyperbolic secant refocusing pairs. We compare performance between this train and the standard composite refocusing train, including with and without DPC, for dual‐module VSI VSASL. We evaluate (1) simulated velocity‐selective profiles and subtraction fidelity across a broad B0/B1+ range, (2) subtraction fidelity in phantoms, and (3) image quality, artifact presence, and gray‐matter perfusion heterogeneity (as measured by the spatial coefficient of variation) in healthy human subjects. Results Adiabatic refocusing significantly improves FT‐VSI robustness to B0/B1+ inhomogeneity for a single label‐control subtraction. Subtraction fidelity is dramatically improved in both simulation and phantoms compared with composite refocusing without DPC, and is similar compared with DPC methods. In humans, marked artifacts seen with the non‐DPC composite refocusing approach are eliminated, corroborated by significantly reduced gray‐matter heterogeneity (via lower spatial coefficient of variation values). Conclusion A novel VSASL labeling train using adiabatic refocusing pulses for VSI was found to reduce artifacts related to B0/B1+ inhomogeneity, thereby providing an alternative to DPC and its associated limitations, which include increased vulnerability to physiological noise and motion, reduced functional MRI applicability, and suboptimal data censoring.